Of some interpretations of Eckhart’s conception of God - Piórczyński, Józef (Hybris, 2013)
The article shows that popular understanding of Eckhart’s God as a personal God is not confirmed by the analysis of Eckhart’s texts, but adopted from the most common concept of God. The article presents three of such interpretations.